The Intercultural Professional - O'Neill, Fiona; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book considers what is at stake for professionals whose work increasingly involves communicating in linguistically and culturally diverse contexts, and argues for the need to better understand the crucial role of languages and cultures in the modern workplace. With a focus on the experience of multilingual professionals, the author's position is that such professionals, exemplified by those who have relocated internationally, deploy their unique linguistic, cultural and intercultural repertoires in their work. This book examines the ways in which professionals interpret and manage their experience of working within and across languages and cultures in ways that create affordances for them, their professional practice, and those who depend on their knowledge and expertise. It will be relevant to undergraduate and postgraduate students undertaking studies in applied linguistics, sociolinguistics, intercultural education and professional communication in any discipline. Fiona O'Neill is an applied linguistics researcher with the Research Centre for Languages and Cultures (RCLC) at the University of South Australia (UniSA).
Chapter 1: Introduction -- Chapter 2: The Contemporary Workplace -- Chapter 3: Why a Narrative Approach? -- Chapter 4: Risks and Affordances -- Chapter 5: Resources and Repertoires -- Chapter 6: Reflection and Responses -- Chapter 7: The Intercultural Professional.
Keywords: Intercultural communication; Communication; Multilingualism; International business enterprises$1 (BCross-cultural studies.s; Cross-cultural psychology; Intercultural Communication; Communication Studies; Multilingualism; Cross-Cultural Management; Cross Cultural Psychology